Non-suicidal self-injury v. attempted suicide: new diagnosis or false dichotomy? - Kapur, N; Cooper, J; O'Connor, R; Hawton, K (2013)
Non-suicidal self-injury (NSSI) is a term that is becoming popular especially in North America and it has been proposed as a new diagnosis in DSM-5. In this paper we consider what self-harm research can tell us about the concept of NSSI and examine the potential pitfalls of introducing NSSI into clinical practice.